Educational pathways and earnings trajectories of second-generation immigrants in Australia: New insights from linked census-administrative data - Nguyen, Ha Trong; Zajac, Tomasz; Tomaszewski, Wojtek; Mitrou, Francis (International Journal of Population Data Science, 2026)
This study employs Australian Census data linked to population-based administrative datasets to explore disparities in educational attainment and earnings trajectories over time among Australian-born children of diverse parental migration backgrounds from mid-adolescence to late-twenties. Non-English Speaking Background (NESB) second-generation immigrants exhibit superior academic outcomes, primarily driven by children of parents from select Asian countries. These individuals are more likely to complete higher education, particularly bachelor’s and master’s degrees, and specialise in fields such as management and commerce, health, natural and physical sciences, and engineering. Children of NESB immigrant parents initially earn less than their peers with Australian-born parents at ages 21–22. However, this gap closes by ages 23–24 and reverses by ages 26–27, with children of NESB fathers out-earning their counterparts by ages 28–29. Conversely, children of English-Speaking Background (ESB) immigrant parents, who exhibit weaker academic performance, also experience lower earnings compared to peers with Australian-born parents. This disparity emerges by ages 22–23 and widens throughout the study period, peaking at ages 28–29. The findings underscore the academic and economic advantages of NESB second-generation immigrants, contrasting with the challenges faced by ESB migrant counterparts, and highlight the importance of considering parental migration backgrounds in understanding post-school outcomes of Australian-born children of immigrant parents.